Political Economy and Forced Displacement : Guidance and Lessons from Nine Country Case Studies - World Bank (Washington, DC, 2014)
This report was produced for the Global Program on Forced Displacement and describes why and how to conduct political economy analysis (PEA) of forced displacement. It also illustrates how PEA may contribute to understanding forced displacement crises with nine case studies: Casamance (Senegal), Colombia, Cote dapos;Ivoire, Democratic Republic of Congo, Liberia, the Philippines, Somalia, South Sudan, and Zimbabwe. Forced displacement is understood here as a situation where persons are forced to leave or flee their homes due to conflict, violence, or human rights violations. The key elements of forced displacement PEAs include: i) a review of the historical context and displacement characteristics; ii) durable solutions prospects; iii) environmental, geographic, social, political, and economic drivers, constraints and opportunities; (iv) needs of the displaced and hosts; v) existing policies, government/institutional context, and operations; and vi) recommendations. Recommendations on development policies and programs that result from a PEA characteristically fall into at least four categories, namely: i) improving access to land, housing and property; ii) reestablishment of livelihoods; iii) improving delivery of services; and iv) strengthening accountable and responsible governance. PEAs of forced displacement analyze the contestation and distribution of power and resources along with the development challenges associated with forced displacement crises. By nature of their marginalization and the frequently protracted nature of their exile, the forcibly displaced are especially vulnerable as power and resources are disputed. The purpose of conducting a PEA on forced displacement is to inform policy dialogue and operations so that the interests of vulnerable forcibly displaced populations and their hosts are effectively accommodated in resource allocation decision-making and in poverty alleviation initiatives. From the earliest design phase to dissemination of the results, the PEA is essentially an exercise in effectively collecting relevant data, analyzing these, and then marketing the analysis and its operational implications to the right stakeholders. This report is intended to be an aid in navigating these decision points and activities and to encourage more frequent and better use of political economy analysis in evaluating and addressing forced displacement.